Diseño de un Manual de Procedimientos para la Liquidación de Convenios con entidades cooperantes en la Coordinación Zonal 7 MIES - Reyes Cordero, Evelyn Nathaly (2023)
The Curricular Integration Work called "DESIGN OF A PROCEDURES MANUAL FOR THE LIQUIDATION OF AGREEMENTS WITH COOPERATING ENTITIES IN THE 7 MIES ZONAL COORDINATION", was carried out as a prerequisite to obtaining the title of Bachelor of Accounting and Auditing, developed in accordance with the established in the Academic Regulations of the National University of Loja. The purpose of this investigation is to design a procedures manual for the liquidation of agreements with Cooperating Entities, which allows the development of operations in a logical, sequential and orderly manner based on their nature, establishing the activities and functions that the team must fulfill. Financial Technician. Said manual constitutes an essential tool since it is a support document that allows the officials of the institution to understand and know in detail the way in which such procedures are executed. To carry out the aforementioned work, as a research instrument, a survey was applied to a sample of six servers from the Financial Administrative Unit, thus gathering information on the level of knowledge of the settlement of agreements to determine the current situation in which entity is found. Different research methods were used that allowed the production of theoretical foundations, thus facilitating the analysis and study of the literary review; which later served to establish value judgments related to the procedures and stages in which the liquidation unfolds, and finally to analyze and interpret the enabling documentation delivered by the cooperating entities to the 7 MIES Zonal Coordination. The manual of procedures for the liquidation of agreements is a tool that allows the authorities and officials of the entity to carry out a sequential order of the liquidation procedures, therefore it is recommended to improve the deficiencies within the process in question, taking into account taking into account the optimization of resources and time, thus making it easier for the institution to execute the programs and projects of agreements efficiently and effectively in each of the operations it carries out.